Răspuns:
(a+3)(a-3) = a²-3²=a²-9
(5+x)(5-x) =5²-x²=25-x²
(4a-2c)(4a+2c)= (4a)² -(2c)²=16a²-4c²
(2y-5x)(2y+5x)=4y²-25x²
(m+3n)(m-3n)=m²-9n²
(t-2z)(t+2z)=t²-4z²
(12a-x)(12a+x)=144a²-x²
(7-4√3)(7+4√3)=49-(4√3)²=49-16·3=49-48=1
(5√3-2√5)(5√3+2√5)=(5√3)²-(2√5)²=25·3-4·5=75-20=55
[tex](\frac{4\sqrt{5} }{3} x-\frac{\sqrt{7} }{2} a)(\frac{4\sqrt{5} }{3} x+\frac{\sqrt{7} }{2} a)=(\frac{4\sqrt{5} }{3}x)^{2} -(\frac{\sqrt{7} }{2}a)^{2} =\frac{16*5}{9} x^{2} -\frac{7}{4}a^{2} =\frac{80}{9} x^{2} -\frac{7}{4} a^{2} =\frac{320x^{2} -63a^{2} }{36}[/tex]
[tex](\frac{1}{2} x-\frac{3}{4} )(\frac{1}{2} x+\frac{3}{4} )=(\frac{1}{2}x )^{2} -(\frac{3}{4})^{2} =\frac{x^{2} }{4} -\frac{9}{16}= \frac{4x^{2} -9}{16}[/tex]
Explicație pas cu pas: